Adhesion and Colonization of the Probiotic Lactobacillus plantarum HC-2 in the Intestine of Litopenaeus Vannamei Are Associated With Bacterial Surface Proteins - Du, Yang; Li, Hao; Shao, Jianchun; Wu, Ting; Xu, WenLong; Hu, Xiaoman; Chen, Jiong (Frontiers in Microbiology, 2022)
Surface proteins are a type of proteins expressed on the surface of bacteria that play an important role in cell wall synthesis, maintenance of cell morphology, and signaling with the host. Our previous study showed that the probiotic Lactobacillus plantarum HC-2 improved the growth performance and immune response of Litopenaeus vannamei. To further investigate the probiotic mechanism, we determined the bacteria’s automatic aggregation ability and surface hydrophobicity of HC-2 after being treated with 5 M lithium chloride (LiCl) and observed the morphology and adhesion of the bacteria to HCT116 cells. The results showed that with the removal of the HC-2 surface protein, the auto-aggregation ability and surface hydrophobicity of HC-2 decreased, and the crude mucus layer coated on the bacteria surface gradually dissociated. The adhesion rate of HC-2 to HCT116 cells decreased from 98.1% to 20.9%. Moreover, a total of 201 unique proteins were identified from the surface proteins’ mixture by mass spectrometry. Several proteins are involved in transcription and translation, biosynthetic or metabolic process, cell cycle or division, cell wall synthesis, and emergency response. Meanwhile, qPCR showed that HC-2 was mainly colonized in the midgut of shrimp, and the colonization numbers were 15 times higher than that in the foregut, while the colonization rate in the hindgut was lower. The adhesion activity measurement showed that the adhesion level of HC-2 to crude intestinal mucus of L. vannamei was higher than that of BSA and Collagen, and the adhesion capacity of bacteria cells decreased with the extension of LiCl-treatment time. Finally, we identified elongation factor Tu, Type I glyceraldehyde-3-phosphate dehydrogenase, Small heat shock protein, 30S ribosomal protein from the surface proteins, which may be the adhesion proteins of HC-2 colonization in the shrimp intestine. The above results indicate that surface proteins play an important role in maintaining cell structure stability and cell adhesion. Surface proteomics analysis contributes to describing potential protein-mediated probiotic-host interactions. The identification of some interacting proteins in this work may be beneficial to further understand the adhesion/colonization mechanism and probiotic properties of L. plantarum HC-2 in the shrimp intestine.